FESTIVAL OF JAPAN AS BRA ZIL’S CULTURAL DIPLOMACY TO JAPAN - Mohamad Fajar Winata (HI 15 UMY 440, 2015)
*440 At the beginning of the 20 century, Japanese immigrants moved to Brazil in great number along with the signing of the Treaty of Amity, Commerce and Navigation coinciding with the beginning of diplomatic relations between Brazil and Japan in November 1895. However, during the hostilities of the World War II period, diplomatic relations between Japan and Brazil were suspended and relations were subsequently re-established in 1952. Foreign direct investment (FDI) from Japan into Brazil grew rapidly in the 1960s which makes Keidanren (the Japanese Business Federation) and Confederação Nacional da Indústria (CNI) successfully supported economic cooperation between the two countries after the restoration of diplomatic relations. In the following period through to the 1980s, business activities between both countries shrank in the 1980s due to a number of factors. This deterioration in business activity between the two countries led the CNI to agree to create a new strategy in order to build stronger partnership between the private sectors of the two countries. This strategy was named the `Alliance for the 21st century` which led Japanese-Brazilian community in Brazil, KENREN (the Federation of Provinces of Japan in Brazil), organizing and holding the inaugural Festival of Japan in order to create mutual understanding between Brazilian and Japanese society in support of the objectives of the strategy. The paper explains the national interest of Brazil towards Japan is served by way of Brazil celebrating its multicultural society at the same time as it embrace its national economical interests. By supporting and maintaining the annual Festival of Japan, the Brazilian government demonstrates how it uses soft power in order to strengthen the bilateral relations between Brazil and Japan. In this case, Brazilian government implements cultural diplomacy theory through an annual festival in order to create mutual understanding between Japanese and Brazilian societies. This paper shows the importance of an annual festival as a tool to realize the national interests of one country towards another country.